2015
DOI: 10.1007/s12262-015-1318-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Tuberculosis

Abstract: Tuberculosis of the pancreas is extremely rare and in most of the cases mimics pancreatic carcinoma. There are a number of case reports on pancreatic tuberculosis with various different presentations, but only a few case series have been published, and most of our knowledge about this disease comes from individual case reports. Patients of pancreatic tuberculosis may remain asymptomatic initially and manifest as an abscess or a mass involving local lymph nodes and usually present with non-specific features. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 51 publications
1
54
0
2
Order By: Relevance
“…Several excellent articles summarized and reviewed clinical manifestations of pancreatic tuberculosis previously. [ 2 , 7 , 12 15 ] The clinical manifestations can be diverse and are commonly caused by the mass in pancreas and/or tuberculous toxaemia. They include abdominal or back pain/discomfort, palpable abdominal lump, jaundice, weight loss, anorexia, fever, night sweats, malaise/weakness/fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several excellent articles summarized and reviewed clinical manifestations of pancreatic tuberculosis previously. [ 2 , 7 , 12 15 ] The clinical manifestations can be diverse and are commonly caused by the mass in pancreas and/or tuberculous toxaemia. They include abdominal or back pain/discomfort, palpable abdominal lump, jaundice, weight loss, anorexia, fever, night sweats, malaise/weakness/fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…They include abdominal or back pain/discomfort, palpable abdominal lump, jaundice, weight loss, anorexia, fever, night sweats, malaise/weakness/fatigue. [ 2 , 7 , 12 15 ] The diagnosis of pancreatic tuberculosis can easily be missed or significantly delayed because of its rarity and lack of specific manifestations. [ 2 , 7 , 11 ] Kim et al [ 11 ] reported that in about 52% of cases, first impression was wrong as pancreatic or peripancreatic malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the diagnosis is confirmed, medical management (antitubercular therapy (ATT)) is the mainstay of the therapy. ATT consists of multidrug chemotherapy and is usually recommended for 6 to 12 months [15]. The disease responds well to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For immunocompetent patients, treatment consists of RIPE therapy for 2 to 4 months followed by continuation of INH and rifampin for a total of 6 to 12 months of treatment. 2 In patients with concern for potential INH resistance, as in this case, substitution of INH with moxifloxacin or concomitant treatment with moxifloxacin is appropriate. Medical therapy is curative for pancreatic and disseminated intra-abdominal TB, although in the setting of lesions resulting in obstruction of the biliary tree, endoscopic stenting may be necessary in the early treatment phase.…”
mentioning
confidence: 99%